Cytotoxic Effects of N, N-Diethyl-Meta-Toluamide (DEET) on Sinonasal Epithelia. Issue 2 (May 2021) - Lee, Jivianne T.; Basak, Saroj
Although the etiology of chronic rhinosinusitis remains unknown, environmental factors including airborne pollutants and toxicants are postulated to contribute to its pathogenesis. However, the precise pathomechanisms with which environmental toxicants may contribute to chronic rhinosinusitis are not fully understood. The purpose of this pilot study is to examine the cytotoxic effects of N, N -diethyl- meta -toluamide (DEET), a commonly used pesticide, on sinonasal epithelial cells (SNECs). Sinus mucosa was obtained from 3 subjects without a history of chronic rhinosinusitis. Cultured SNECs were exposed to various concentrations of DEET (0-5 mM) for 6 days. Cell viability, proliferation, and morphologic changes were assessed using the MTT colorimetric dye assay and the Incucyte Live Cell Monitoring System. Statistically significant dose-dependent reduction in cell viability and proliferation was observed between exposure and control groups ( P < .05) at all concentrations tested. Dose-dependent cellular morphological changes were also seen. These findings indicate that DEET exposure induces dose-dependent cytotoxicity in sinonasal epithelia.